Antibacterial Activity of Nanomaterials - Ana María Díez-Pascual (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Bacterial proliferation is a severe and increasing concern in everyday life, which accounts for important damage in a number of industries, from textile and marine transport to medicine and food packaging. Despite the huge efforts by academic and industry researchers, a universal solution for controlling bacterial colonization has not been established yet. In this regard, nanomaterials are more and more used to target bacteria as an alternative to antibiotics. Examples include the use of nanomaterials in antibacterial coatings for implantable devices and other materials to prevent infection and promote wound healing and in antibiotic delivery systems to treat diseases. By exploiting the excellent antibacterial properties of some materials at the nanoscale, namely ZnO, TiO2, Ag, Au, nanodiamond and graphene, effective strategies for the prevention of infections can be developed. The main focus of this book is, therefore, to present selected examples of the most recent advances in the synthesis, characterization, and applications of nanomaterials with antibacterial activity. The book is addressed to scientists and industry researchers, as well as to master and degree students in chemistry, pharmacy, bioengineering, biology and materials science. The Editor would like to thank the staff of Nanomaterials Editorial Office for the constant help and support.